ISOLASI PROTEIN SELAMA PROSES PENGAMBILAN KITIN DARI KULIT UDANG - Kherliyanda Febriani; Fitri Hariani Nurza; Iriany (Jurnal Teknik Kimia USU, 2016)
Shrimp is one of the Indonesia fishery commodities with high economic value. The production of shrimp shells is usually 40-45% from crude shrimp. Shrimp shell contain protein, chitin, minerals and carotenoids. It is very potential to be used as materials for isolation of protein.This experiment is to determine factors that effect protein recovery and optimize deproteination processconditions to produce high yield of protein. The design of experiment used response surface methodology. It is 2 steps consist of deproteination and protein extraction process using shrimp shells and KOH solution in comparison 1:10 (w/v). The concentration of KOH are1,3 M; 2 M; 3 M; 4 M; 4,7 M. The reaction temperatures are37 oC; 40 oC; 45 oC; 50 oC; 53 oCand the reaction times are 40 minutes, 60 minutes, 90 minutes, 120 minutes, 140 minutes. Reaction temperature is the main factor influence protein recovery process. The highest protein yield obtained is 64,5826 % with protein content is 86,24% using KOH solution 2,98 M, reaction temperature 45,76 ºC and reaction time 90,51 minute. Economic potential by protein recovery during isolation of chitin from shrimp shells is profitable.